Rancang Bangun Sistem Informasi Pengelolaan Transaksi Penjualan dan Persediaan Bahan Makanan Berbasis Web Menggunakan Bootstrap dan Framework Codeigniter - Sari, Aulia Kurnia; Zakaria, Hadi (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Bakso Gian Restaurant is one of the famous meatball restaurants in the Bogor area. Bakso Gian restaurant sells various types of meatballs, such as original meatballs, egg meatballs. Not only meatballs, Bakso Gian Restaurant also sells various other types of food and drinks such as original chicken noodles and various types of juices and packaged drinks. The financial reports of the Bakso Gian Restaurant have problems in terms of recording sales and inventory data, making reports on sales of incoming and outgoing food supplies there are still frequent errors, where the financial reports do not match the incoming and outgoing inventory. To overcome these problems the authors conducted research to create an application that helps restaurants to make it easier to get reports quickly and accurately. In this study the authors used bootstrap and the codeigniter framework, as well as a MySQL database as data storage for incoming and outgoing goods reports. And the author uses the Waterfall model in making the design flow. It is hoped that the design application for this web-based sales transaction and food supply information system design can make it easier for employees to input and record incoming and outgoing food ingredients at the Bakso Gian Restaurant so that managers and employees no longer need to write or check manually.